Functional interaction and colocalization of the herpes simplex virus 1 major regulatory protein ICP4 with EAP, a nucleolar-ribosomal protein. - Leopardi, R (1996)
The herpes simplex virus 1 infected cell protein 4 (ICP4) binds to DNA and regulates gene expression both positively and negatively. EAP (Epstein-Barr virus-encoded small nuclear RNA-associated protein) binds to small nonpolyadenylylated nuclear RNAs and is found in nucleoli and in ribosomes, where it is also known as L22. We report that EAP interacts with a domain of ICP4 that is known to bind viral DNA response elements and transcriptional factors. In a gel-shift assay, a glutathione S-transferase (GST)-EAP fusion protein disrupted the binding of ICP4 to its cognate site on DNA in a dose-dependent manner. This effect appeared to be specifically due to EAP binding to ICP4 because (i) GST alone did not alter the binding of ICP4 to DNA, (ii) GST-EAP did not bind to the probe DNA, and (iii) GST-EAP did not influence the binding of the alpha gene trans-inducing factor (alphaTIF or VP16) to its DNA cognate site. Early in infection, ICP4 was dispersed throughout the nucleoplasm, whereas EAP was localized to the nucleoli. Late in infection, EAP was translocated from nucleoli and colocalized with ICP4 in small, dense nuclear structures. The formation of dense structures and the colocalization of EAP and ICP4 did not occur if virus DNA synthesis and late gene expression were prevented by the infection of cells at the nonpermissive temperature with a mutant virus defective in DNA synthesis, or in cells infected and maintained in the presence of phosphonoacetate, which is an inhibitor of viral DNA synthesis. These results suggest that the translocation of EAP from the nucleolus to the nucleoplasm is a viral function and that EAP plays a role in the regulatory functions expressed by ICP4.